PENGARUH ALAT PEMBAYARAN MENGGUNAKAN KARTU (APMK) DAN DANA FLOAT TERHADAP VELOCITY OF MONEY DI INDONESIA PERIODE 2015.1 – 2024.12: The Effect Of Payment Instruments Using Cards (APMK) And Float Funds On The Velocity Of Money In Indonesia In The Period 2015.1 – 2024.12 - Handriani, Lhatifah Fitria; Chaidir, Taufiq; Suriadi, Irwan (Ganec Swara, 2025)
The objective of this study is to analyze the effect of transaction values using cards (Card Payment Instruments/APMK), namely credit cards and debit cards, as well as float funds on the Velocity of Money (VOM) in Indonesia. This study employs a quantitative approach using descriptive methods, utilizing secondary data on credit card transaction values, debit card transaction values, float funds, and VOM over the period 2015–2024. The data sources were obtained from the official websites of the Bank of Indonesia (BI) and the Central Statistics Agency (BPS). The analysis method employed is the Error Correction Model (ECM) to observe short-term and long-term dynamics. The findings of the study suggest that, over an extended period, credit card transaction values (KK) and float funds (DF) exert a positive and significant influence on VOM, while debit card transaction values (KD) prove to be statistically insignificant. In contrast, in the short term, float funds (D(DF)) exert a negative and significant influence on changes in VOM, while changes in credit cards (D(KK)) and debit cards (D(KD)) do not demonstrate a statistically significant effect. Furthermore, the lagged value of credit cards exhibits close to significant at the 10% level, suggesting a gradual adjustment effect on VOM. These findings suggest that policies promoting the optimization of credit cards and the management of float liquidity can encourage money circulation in the long term. However, the impact of debit cards must be carefully considered to avoid directly suppressing the speed of money circulation in the short term. Thus, the evolution of non-cash payment systems must strike a balance between transaction efficiency and its implications for national monetary dynamics.